The Effectiveness of Social Sciences Learning with Problem Based Learning (PBL) Assisted as Prezi Media on Critical Thinking Ability and Conceptual Understanding of Fifth Grade Elementary School Student - Gesti Sekar Santiwi; Rusdarti Rusdarti; Wagiran Wagiran (Universitas Negeri Semarang, 2022)
The purpose of this study was to improve critical thinking skills and conceptual understanding of fifth grade elementary school students in learning Social Sciences using the prezi media-assisted Problem Based Learning (PBL) model. The method used is quantitative research with experimental research types. The data collection instruments used were observation sheets, tests, and documentation. The subjects of this study were the fifth grade students of SDN Karangwuni 01 as the experimental class and the fifth grade students of SDN Karangwuni 03 as the control class. The results of the study show that the PBL model assisted by Prezi media is valid for use in social studies learning in fifth grade of elementary school. Effective in improving students' critical thinking skills, as evidenced by the acquisition of N-Gain is 0.69 in the medium category. The PBL model assisted by Prezi media is effective in increasing students' understanding of concepts. Evidenced by the acquisition of N-Gain is 0.72 in the high category. Based on these results, it can be concluded that social studies learning with the PBL model assisted by Prezi media is effective in improving critical thinking skills and conceptual understanding of elementary school students.